Zinc intake during the pregnancy increases the proliferation at ventricular zone of the newborn brain - Azman, Mohd S.; Wan Saudi, Wan S.; Ilhami, Mohammad; Abdul Mutalib, Mohd Sokhini; Rahman, Muhammad Tariqur (Maney Publishing, 2009)
Neurogenesis involves cell proliferation, cell cycle arrest, differentiation, migration and the natural developmental death of the neural precursors. These processes are highly co-ordinated and governed by cell-cycle genes and neural transcription factors. Zn plays a crucial role as a functional and structural component of enzymes and transcription factors and components of the intracellular signaling pathway associated with the regulation of cell proliferation. The influence of additional Zn intake during pregnancy on the neuronal proliferation at ventricular zone of the developing fetus has been studied. Pups delivered by the group of mice provided with drinking water with 4.0 mM Zn supplement throughout pregnancy contained an increased number of proliferating neurons in the ventricular zone at P0 compared to those delivered by the mice provided with drinking water without any Zn supplement. This finding provides direct evidence to support the notion that maternal Zn levels influence the development of the nervous system of the offspring.